Antiangiogenic potential of an olive oil extract: insights from a proteomic study - Marrero Capitán, Ana Dácil; Cárdenas García, Casimiro; Castilla, Laura; Ortega Vidal, Juan; Rodríguez-Quesada, Ana María; Martínez-Póveda, Beatriz Amparo; Medina-Torres, Miguel Ángel (ACS, 2024)
Extra virgin olive oil (EVOO), a staple of the Mediterranean diet, is rich in phenolic compounds recognized for their potent bioactive effects, including anticancer and anti-inflammatory properties. However, its effects on vascular health remain relatively unexplored. In this study, we examined the impact of a “picual” EVOO extract from Jaén, Spain, on endothelial cells. Proteomic analysis revealed the modulation of angiogenesis-related processes. In subsequent in vitro experiments, the EVOO extract inhibited endothelial cell migration, adhesion, invasion, ECM degradation, and tube formation while inducing apoptosis. These results provide robust evidence of the extract’s antiangiogenic potential. Our findings highlight the potential of EVOO extracts in mitigating angiogenesis-related pathologies, such as cancer, macular degeneration, and diabetic retinopathy.
Keywords: Antiangiogénicos; Aceite de oliva; Virgin olive oil; Mediterranean diet; Natural extract; Angiogenesis; Chemoprevention; Functional food